Karttikeya - Temples of India Project Team (Jio Institute, 2024)
Broken image of a two-armed male deity with three heads and faces. The central principal head wears a kakapaksha (hairstyle with two side locks with a clearly visible middle section), while the others have small mukutas. He is adorned in a vanamala. Vahana peacock is shown near the right leg. The halo is of lotus petals surrounded by pearls.